Influence of different processing conditions on phenolic profile, antioxidant, and anti-cholinesterase activities of spinach, and mustard leaves - Arif Mehmood; Alam Zeb; Muhammad Ayaz (CyTA - Journal of Food)
The effect of domestic cooking techniques such as boiling, frying, microwaving, and freezing on the phenolic profile of spinach, and mustard was studied using high performance liquid chromatography with diode array detection (HPLC-DAD). Nitric oxide, superoxide anion scavenging activity, and anti-choline esterase activity were studied using spectroscopic methods. Results showed 12 phenolic compounds in spinach and 13 in mustard leaves. Microwaving significantly enhanced the amounts of most of the phenolic compounds. Conversely, boiling has an enervating effect on the amounts of phenolic compounds. Raw spinach and mustard leaves have the highest nitric oxide inhibition activities of 42.4 and 62.7%, respectively, followed by microwaving and freezing. Similarly, the highest % superoxide anion scavenging activity was determined in raw spinach and mustard. The applied cooking techniques had deleterious effects on anti-cholinesterase activities. In conclusion, different processing conditions affected phenolic availability, and the antioxidant and anti-cholinesterase activities of the selected vegetable leaves.